Families and states in Western Europe - Skinner, Quentin (Cambridge University Press, 2011)
"This collection of essays traces the relationship between families and states in the major countries of Western Europe since 1945, examining the power of states to shape family life and the capacity of families to influence states. Written by an exceptionally distinguished team of scholars, Families and States in Western Europe follows many narratives, allowing comparisons to be drawn between different countries. The essays point to numerous convergences, illustrating how states have coped with common problems arising at the level of family life, and exploring issues such as secularism, the pressure of multiculturalist demands and the growing rejection of welfare state principles. Families and States in Western Europe will be of interest to anyone analysing relations between civil society and the modern democratic state, and the place of the family within this relationship. This collection makes a significant contribution to current political theory and to our understanding of European family life in its many different forms"--